Therapeutic aspects of Connection to Country and cultural landscapes among Aboriginal peoples from the Stolen Generations living in urban NSW, Australia - Aryati Yashadhana; Ted Fields; Edgar Liu; Nina Serova; Michelle O'Leary; Gail Kenning; Volker Kuchelmeister; Jonathan Lockhart; Evelyne de Leeuw (Sax Institute, 2023)
Objectives and importance of the study: Most older Aboriginal peoples live in urban locations. Many of these people were displaced by the policies and practices that produced the Stolen Generations. As a result, access to 'Country' and cultural landscapes that are minimally impacted by urbanisation can be limited for older Aboriginal peoples, restricting the health and wellbeing benefits these environments promote. Study type: Qualitative study. Methods: Our study worked collaboratively with Aboriginal traditional cultural knowledge holders to observe and analyse how participation in a 'cultural camp' on a Yuwaalaraay sacred site in New South Wales (NSW), Australia, impacted wellbeing and connection to place among older Aboriginal people who were survivors or descendants of the Stolen Generations. Results: Eight participants (three women; five men) attended the cultural camp and took part in the yarning circle. Thematic analysis of a yarning circle uncovered memories of traumatic experiences of institutionalisation, including abuse and loss of Country, community, and culture. Experiences of the cultural camp generated a sense of reconnection, cultural pride, wellbeing and place attachment. The sensory experience of Country emphasised a sense of belonging and healing. Conclusions: Our findings reflect the importance of sensory-led experiences on Country for older urban Aboriginal peoples and reinforce previous evidence on the 'therapeutic' aspects of culture and natural landscapes minimally impacted by colonisation. Policies and resources supporting grassroots initiatives such as Aboriginal cultural camps are needed to ensure accessibility for older Aboriginal peoples living in urban places.